A educação de surdos na cidade de Belo Horizonte: uma perspectiva histórica - Tales Douglas Moreira Nogueira (2021)
The Deaf education is a complex issue and involves a history marked by misunderstandings and social struggles. The Milan Congress, held in 1880 and attended by educators for the deaf, proclaimed that oral language was more appropriate than sign. This position ended up having reflexes that went on for quite some time. In Brazil, it was no different. Studies carried out on the National Institute of Education for the Deaf (INES) by Morais and Cruz, 2020; Strobel, 2009; Goldfeld, 1997, among others, highlight the prevalence of oralism. This research aimed to investigate the education of the deaf, taking as a background the phases of special education proposed by Borges and Campos (2018)), that is, from special classes to Inclusive Education, in the city of Belo Horizonte, Minas Gerais. The research was developed from the historical perspective of Le Goff (1990), also taking the guidelines of Nosella and Buffa (2013) as a reference, based on document analysis, mainly from primary sources such as the Exceptional Childhood bulletins, the correspondence between Helena Antipoff and Helena Dias Carneiro, and the records of the Pestalozzi State School. In addition, a semi-directed interview was carried out with two important characters in the history of deaf education in Minas Gerais, Professor Antônio Campos de Abreu and Professor Maria Barbosa Coelho. The Pestalozzi Institute (1935) was one of the first public institutions dedicated to teaching deaf people in Belo Horizonte. Helena Antipoff, the founder of the Institute, played a fundamental role in the schooling of these children, as did Ester Assumpção. In the bulletins published by the Pestalozzi Society of Minas Gerais, it was possible to see the influence of oralism. Antipoff's correspondence revealed the proximity to INES and the medical records, through the silence in relation to educational practices, revealed little emphasis on formal educational aspects. Finally, the interviews with a former deaf teacher from the Pestalozzi State School and with a militant of the cause, showed the importance of social movements in the search for rights. The study's conclusion demonstrates that the paradigm shift from the medical model to the social model of disability and, finally, the strong attempt for the right to bilingualism, which was fundamental for the deaf community to gain rights.